Facies Analysis, Sedimentology and Paleocurrent of The Quaternary Nenering Formation, Pengkalan Hulu, Malaysia - Yuniarti Ulfa; Evonne Hooi Rong Yu; Ooi Cheng Kit (EKSPLORIUM, 2014)
Nenering Formation is essentially made up of semi-consolidated sediments, which are divided into basal conglomerate beds, conglomeratic sandstone, cross-bedded sandstone, and siltstone to muddy layers facies. It is overlie unconformable to the Berapit Formation, but conformable to the Kroh and Grik Formations. The stratigraphy of Nenering Formation is a fining upwards sequence where the thickness of conglomerate beds become thinner upwards and become thicker for conglomeratic sandstone. The thickness varies from 0.5 m to tenths of meters. The more sandy in the upper portion (cross-bedded sandstone) overlie with thin siltstone and mudstone facies. The clast and grain composition suggested that the material making up the sedimentary sequence were derived predominantly from the erosion of granitoid rocks and sedimentary and metamorphic rocks constitute a minor provenance. Imbrications and the trend sizes of clasts indicate that the palaeo-current flow toward northeast. Cross bedding that was found in conglomerate and sandstone indicates the main channel depositional environment. The sequence stratigraphy of this area match with the Saskatchewan fluvial braided channel model. Formasi Nenering tersusun atas sedimen semi-terkonsolidasi yang terdiri atas lapisan basal konglomerat, batupasir konglomeratik, batupasir berlapisan silang siur, batulanau hingga fasies berlapisan lempung. Formasi Nenering terletak tidak selaras di atas Formasi Berapit, tetapi terletak selaras di atas Formasi Kroh dan Formasi Grik. Stratigrafi Formasi Nenering adalah menghalus ke atas, dimana ketebalan batuan konglomerat semakin menipis ke arah atas, sedangkan batupasir konglomeratik menjadi menebal ke arah atas. Ketebalan perlapisan berkisar pada 0,5 meter hingga puluhan meter. Komposisi pasir yang lebih dominan pada bagian atas (batupasir silang siur) terletak di atas fasies lapisan tipis batulanau dan batulempung. Komposisi butiran dan klastika menunjukkan bahwa material yang menyusun sekuen sedimen didominasi berasal dari erosi batuan granitik, batuan sedimen dan sedikit dari batuan metamorf. Indikasi imbrikasi dan kecenderungan perubahan ukuran material klastika menunjukkan bahwa aliran arus purba mengarah ke timur laut, sedangkan perlapisan silang siur pada batuan konglomerat dan batupasir mengindikasikan lingkungan pengendapan berupa sungai. Sekuen stratigrafi di daerah ini sesuai dengan model lingkungan pengendapan sungai teranyam fluvial Saskatchewan.